Investigation into a Possible Association between Telomere Length in Prostate Cancer patients and Non prostate cancer patients - Martwachira, Karuha; Kaewtunjai, Navakun; Tuntiwechapikul, Wirote; Lojanapiwat, Bannakij (Insight Urology, 2019)
Investigation into a Possible Association between Telomere Length in Prostate Cancer patients and Non prostate cancer patients Karuha Martwachira1, Navakun Kaewtunjai2, Wirote Tuntiwechapikul2, Bannakij Lojanapiwat1 1Division of Urology, Department of Surgery, Faculty of Medicine, Chiang Mai University, Thailand 2Department of Biochemistry, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand Abstract Background Aging is one of the non modifiable risk factors for many medical conditions including malignancy, metabolic syndrome and cardiovascular disease. Telomeres are the protective structures at either end of each chromosome. The length of the telomere is known to be a marker of biological aging. Telomeres in normal cells shorten with each cell division resulting in cellular senescence and cell death. Cancers cell have protective mechanism to prevent cell death. Several studies have shown that shorter leukocyte telomeres predict a high risk of malignancy Objective To investigate a possible association between leukocyte telomere length (LTL) in prostate cancer patients and that in non prostate cancer patients. Methods Enrollment criteria for the study were: patients over 50 years of age who were being screened for prostate cancer or had an abnormal digital rectal examination, those whose serum PSA was more than 4 ng/dL or had increased more than 0.75 ng/dL per year Clinical data and laboratory data were recorded and participants were divided into 2 groups a prostatic cancer patients group and a non prostatic cancer group as dictated by the pathological findings. We compared the leukocyte telomere length in each group. The primary outcome was the LTL in the prostatic and non prostatic cancer group. The secondary outcome was what affected the LTL in Prostate cancer patients. Univariable and multiple linear regression analytical outcomes were compared. A p-value < 0.05 was deemed to be statistically significant. Results 200 patients were included in the study, 87 in the prostatic cancer group and 113 in the non prostatic cancer group. Baseline characteristic of participants are summarised in Table 1. The mean age of the cancer patients was 70.09 years and 67.61 years in non cancer group The mean LTL was 5.37 in the prostatic cancer group and 5.40 in the non prostatic cancer group (p=0.736). The mean serum PSA was significantly higher in the prostatic cancer group compared with the non prostatic cancer (307.76 vs 11.80, respectively) (p<0.001). This analysis showed that older age (60 years plus) was significantly associated with shorter leukocyte telomere length (P=0.01). However other factors were not associated with leukocyte telomere length (Table 2). Conclusions In this prospective study leukocyte telomere length was not significantly different between the prostatic cancer group and the non prostatic cancer group. Aging (60 years old plus) and distant organ metastasis were significantly associated with leukocyte telomere length